Dirac equation with spinors using Clifford algebra Cl (3,1) approach - Shabnam Jahan Ansari,; V. R. Lakshmi Gorty, (Utilitas Mathematica, 2025)
The Dirac equation and spinors are developed in Clifford algebra Cl (3,1) using the representation of the Gamma matrices. Gamma and Pauli matrices in Cl (3,1) are used to show applications in Clifford algebra using the Clifford-wavelet function. The graphical representation of Gamma matrices is interpreted. Majorana spinors relation is given with charge conjugation in the Clifford algebra sense.